The influence of Santa Teresa de Jesús on contemporary spanish theater: writing, confession and subversive deliriousness - Blasco Mena, M.ª Dolores (Philologia Hispalensis, 2022)
Saint Teresa of Ávila (1515-1582), patron saint of writers, showed from an early age a great facility for storytelling and persuasion, as well as a great desire to be the protagonist of her own life at a time when women were only eligible for secondary roles. This article investigates the life and work of this writer, and the influence that her figure has on contemporary literature, fundamentally on contemporary Spanish theater. The beauty with which Teresa de Cepeda will narrate her encounters with the Beloved, will not only be a source of inspiration for multiple artists on and off the stage, but will also manage to change the religious reality of her time and make her the leader of a new order, the Discalced Carmelite nuns, at a time when Catholicism possessed great political and economic power.